PM-ISD traceability metrics enhance reliability assessment for safety-critical systems development processes: a case study of oil and gas well drilling project - Thawaba, Abdulaziz Ahmed; Ramli, Azizul Azhar; Md. Fudzee, Mohd. Farhan (IEEE, 2021)
Safety-Critical Systems (SCS) perform an important and influential role in our daily activity, but any faults during their operation could result in loss of life, human injury, environmental damage or major financial loss. SCS systems deploy in many important filed that we use daily, such as transportation, medical, space, and nuclear systems. According to several studies, more than 59% of SCS failures could be avoided by improving performance during the development processes. Therefore, this paper discusses how to reduce the failure cause of SCS systems by enhancing the reliability assessment of development processes using PM-ISD Traceability Metrics. PMISD is a measurement framework that contains several metrics used to track or forecast development processes. The PM-ISD Traceability Metrics tracked the actual results of the oil and gas development processes shown a failure tolerance rate of 99.27% and a reliability rate of 98.3% for tasks that met the standards. For tracking with time-weighted terminate, the fault tolerance rate can be increased to 99.88% and the reliability rate can be increased to 99.5% at the completion stage. PM-ISD is a suitable measurement framework for developing SCS as it helps to track the achievement of standards, which is reflected in minimizing errors during the development stages.